1999
DOI: 10.1177/107110079902000309
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Evaluation of the Subtalar Joint: Does Sinus Tarsi Syndrome Exist?

Abstract: This is a retrospective review of 49 subtalar arthroscopies performed between 1989 and 1996. Patients were evaluated in the following areas: (1) preoperative diagnosis, (2) preoperative tests and clinical evaluation, (3) intraoperative findings, (4) postoperative diagnosis,(5) complications, and (6) clinical outcome. Particular attention was paid to the accuracy of the preoperative diagnosis, subtalar instability, intraoperative findings in sinus tarsi syndrome, and clinical outcome. Overall, this study demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(61 citation statements)
references
References 4 publications
0
57
1
3
Order By: Relevance
“…Moreover, some of these ligamentous structures might have been confused with each other due to their adjacent positions. The ITCL has been described with different morphologies, including a V shape, an inverted Y shape, a veil extending across the tarsal canal, an oblique band, and a two-layered structure [ 7 , 8 , 14 , 18 ]. A consensus on the description of the ITCL is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some of these ligamentous structures might have been confused with each other due to their adjacent positions. The ITCL has been described with different morphologies, including a V shape, an inverted Y shape, a veil extending across the tarsal canal, an oblique band, and a two-layered structure [ 7 , 8 , 14 , 18 ]. A consensus on the description of the ITCL is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Although noninvasive distraction may improve accessibility in posterior arthroscopy 2,35 and even wire-based invasive distraction may have its place in specific cases, 2,32,57,58,63 one should nonetheless take all possible means to minimize complication rate, which has been shown to be higher in procedures using invasive or noninvasive distraction. 3,7,11,12,14,17,18,21,25,29,39,43,45,52,54,55,58 Though most talar OCDs may be addressed though anterior arthroscopy, there can arise situations in which the location of the specific OCD may warrant a posterior approach. As the majority of OCDs treated by arthroscopic approaches commonly do not exceed 1 cm 2 , 19,38,60 the authors feel certain that the results shown in this study are clinically significant as the information presented may affect preoperative planning and the arthroscopic treatment of some talar lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous papers have morphologically described the ITCL as a broad, flattened band 9,11,17,30 or a V-shaped ligament in the tarsal canal. 7 In terms of the layer of the ITCL, it has been described as part of the capsule of the talocalcaneonavicular joint 29 or to be located between the capsules of the posterior talocalcaneal and talocalcaneonavicular joints. 30 The medial root of the IER has been described as being separated into 2 or 3 components.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical knowledge of the subtalar joint remains controversial due to complexity in nomenclature, shape, and functions of the ligamentous structures, including the ITCL, cervical ligament (CL), and inferior extensor retinaculum (IER). 7,9,15,24,27,29,30,34 The tarsal canal and sinus are described as small funnel-shaped areas situated anterior to the posterior talocalcaneal joint and posterior to the talocalcaneonavicular joint, respectively. 4,9,30 The larger tarsal sinus opens laterally, whereas the stemlike tarsal canal extends medially, posterior to the sustentaculum tali.…”
Section: Introductionmentioning
confidence: 99%